Characteristics of Patients Reporting Presumed Problematic Drinking Behavior After Gastric Bypass: Exploring Long-Term Data From the BAROBS Study - Strømmen, Magnus; Klöckner, Christian Andreas; Bjerkan, Kirsti Kverndokk; Græslie, Hallvard; Hoff, Dag Arne Lihaug; Johnsen, Gjermund; Kulseng, Bård; Mårvik, Ronald; Nymo, Siren; Sandvik, Jorunn (Frontiers in Endocrinology, 2021)
Objective: To explore patients’ long-term experiences with drinking alcohol after Roux-n-Y gastric bypass (RYGB) for conceptualizing what may indicate problematic drinking behavior after bariatric surgery. Study Design: Three-center, observational study. Patients: 546 adult patients undergoing RYGB in the period 2003-2009 in Norway. Main Outcome Measures: Self-reported data on drinking behavior and experiences related to alcohol collected 10-15 years after surgery. Results: Out of the 959 patients undergoing RYGB in the period, 29 were diseased and 546 participated in this follow-up study (58.7%). Focusing on suspicious changes in drinking behaviour, 8.8% reported drinking more, 11.5% consumed alcohol at least twice a week, and 10.6% consumed at a minimum of 6 units of alcohol at a frequency of at least once monthly. The nature of hangovers had changed for about a third of the patients, with 21.6% reporting these to feel weaker or absent. Repeated alcoholic blackouts were reported by 11.9%. A subgroup of the patients were categorized as displaying presumed problematic drinking behaviour (PPDB). Among the PPDB-men there was a significant association to having had a fall last year (6 (100.0%) PPDB-patients vs. 30 (29.7%) non-PPDB, p<.001). Among the PPDB-women, there was a significant association to having had alcohol problems prior to surgery (7 (70.0%) PPDB-patients vs. 67 (17.7%) non-PPDB, p<.001). Less significant associations to PPDB reported for explorative purposes were lack of patient education (men) (16 (26.2%) PPDB-patients vs. 8 (61.5%) non-PPDB, p=.014); more than 3 months persistent musculoskeletal pain (women) (45 (15.3%) PPDB-patients vs. 29 (24.6%) non-PPDB, p=.026); subjective problems with memory (women) (58 (20.7%) PPDB-patients vs. 10 (9.1%) non-PPDB, p=.006); and, receiving professional help for mental problems last 12 months (women) (29 (22.7%) PPDB-patients vs. 45 (14.7%) non-PPDB, p=.043). Conclusion: A subset of patients display drinking behaviours that may be consistent with postsurgical alcohol problems. Screening instruments like AUDIT may not be sufficiently specific to capture several risk behaviours occurring after bariatric surgery.